Examining Islamophobia in Kani’s Journeys of Hearts and Arrows Using Fairclough Framework - Mouhine, Aymen; Khristianto, Khristianto (Language Horizon: Journal of Language Studies, 2023)
This article employs Norman Fairclough’s critical discourse analysis framework to dissect the manifestation of Islamophobia in Yassin Kani’s novel, "The Travels of Hearts and Arrows," set against the backdrop of contemporary Spain. Through an in-depth examination of text, discourse practices, and societal frameworks, the study unravels the nuanced layers of anti-Islamic sentiments prevalent in Spanish society. The analysis reveals how linguistic structures in the novel perpetuate negative stereotypes, reflecting and shaping societal biases. Furthermore, the author’s strategic use of Arabic in the text suggests a deliberate attempt to convey the narrative to Arab readers, highlighting a discursive practice aimed at reshaping public opinion beyond the immediate Spanish readership. Drawing on Fairclough’s situational, institutional, and social levels of analysis, the study traces the historical roots of Islamophobia in Spain, emphasizing the role of media institutions in perpetuating negative stereotypes. This research contributes to the understanding of Islamophobia within Spain and underscores the broader applicability of critical discourse analysis in unraveling complex societal issues embedded in language. The findings hold implications for fostering tolerance and dismantling stereotypes in diverse societies.